The Role Leadership in Creating Work Life Balance - Sylvia, Margareth; Iswati, Sri; Anshori, Muslich (RSF Conference Series: Business, Management and Social Sciences, 2024)
This research aims to map the development of Work-Life Balance (WLB) research and its relationship to the context of leadership. In total, 777 scientific articles indexed in Scopus were used as the database. Analysis was conducted using a bibliometric approach to map the author, source, and document details. The results found that WLB research began in 1993 and experienced significant increases during and after COVID-19. 2865 authors are dominated by research in developed countries and the health sector. This study found that transformational, servant, and e-leadership leadership styles are the most researched styles for realizing WLB. Apart from that, WLB is widely discussed in a gender context in which women, both as employees and leaders, still find it challenging to achieve WLB due to the high intensity of work-family conflict. This research is essential for human resource management (HRM) when reviewing operational arrangements and leadership styles. HRM must also make more specific interventions for female workers to achieve WLB in their careers.